Plant growth-enhancing traits of rhizobacteria isolated from brinjal, okra, and leaf mustard - Umar, Amirul H.M.; Zakry, Fitri A.A. (Japanese Society for Root Research, 2023)
Exploring new plant-associated rhizobacteria and reintroducing them to the crop-soil environment is among the strategies to reverse the declining quality of the agricultural soil environment. A total of 340 isolates were recovered from the rhizospheres of okra (Abelmoschus esculentus), leaf mustard (Brassica juncea), and brinjal (Solanum melongena). From among the total, 155 isolates (45.59%) were diazotrophs, and 122 (35.88%) and 127 (37.35%) were isolates with the solubilising activity of phosphate and potassium, respectively. Thirteen of the most promising isolates were identified by gas chromatography for their cellular fatty acid methyl esters: Escherichia vulneris (TC19), Klebsiella pneumoniae (BA5, SA19, SB22), Pantoea ananatis (TC22), Pseudomonas aeruginosa (BA46), Pseudomonas putida (BA29, BA37, SC5, SC14), Salmonella bongori (BC17), Salmonella enterica (BB2), and Shigella dysenteriae (BA16). Three Pseudomonas strains viz. P. aeruginosa BA46 and P. putida BA37 and SC5 were selected after enhancing root elongation and vigour of lettuce seedlings. The American lettuce growth performance in the non-circulating hydroponic system was established. The inoculation with rhizobacteria strains, SC5 and BA46, stimulated shoot and root biomass over uninoculated control plants. The inoculation of lettuce plants with isolates BA37, BA46 and SC5, produced significantly longer roots compared to uninoculated control plants. This study indicates the potential use of the strains BA46 and SC5 as candidates for the formulation and production of hydroponic nutrient solution fortified with beneficial bacteria.